Gene Frequency and Prevalence of ABO and Rh D Blood Group Systems among Libyan Donors and Patients of Jabal Nafusa Region, Libya - Regeai, Sassia; Sumaya Grenat (AlQalam Journal of Medical and Applied Sciences, 2024)
The ABO and Rh D/d blood group systems have significant medical and genetic importance. In Libya, several studies had been conducted on the distribution of the ABO and Rh D/d blood group systems in different regions of the country. However, there are many regions in Libya that have not yet been studied. Therefore, the aim of this study was to determine the gene frequency and prevalence of ABO and Rh D/d blood group systems among Libyan donors and patients of Jabal Nafusa region in Zintan, Alrujban, and Jadu cities north western of Libya; in addition to Tripoli city. This was a retrospective study that included only Libyans attending the Central Blood Bank in Zintan, Alrujban Clinic in Alrujban, Jadu Medical Analysis Laboratory in Jadu, and Al-Khadra Hospital in Tripoli. The ABO grouping and the Rh typing was done by the standard slide method using commercial blood grouping anti-A, anti-B and anti-D. Data was analyzed using descriptive statistics and Hardy–Weinberg equilibrium law. The overall results of this study show that the most prevalent ABO blood group was O (33.68%), followed by A (26.27%), B (21.31%), and AB (18.74%); which cluster into three categories: O>A>B>AB (Zintan and Alrujban cluster), A>O>B>AB (Tripoli cluster), O>AB>B>A (Jadu cluster). The highest prevalence of A+ (29.35%), B+ (19.73%) and A- (8.74%), B- (9.47%) was found in Tripoli and Jadu, respectively. Jadu had the highest prevalence of AB+ (14.86%) and AB- (11.37%). The highest percentage of O+ (46.92%) and Rh D+ (91.64%), O- (12.97%) and Rh d- (42.56%) was observed in Zintan and Jadu, respectively. The occurrence of considerable percentages of O- and AB- blood groups in Jadu indicated significant medical implications for healthcare blood transfusion services. The gene frequency of ABO and Rh D for A, B, O, D+, and d- alleles respectively are: 0.1795, 0.1025, 0.7180, 0.7109, and 0.2891 in Zintan; 0.2013, 0.0762, 0.7225, 0.5817, and 0.4183 in Alrujban; 0.1860, 0.1892, 0.6248, 0.3476, and 0.6525 in Jadu; 0.2693, 0.1885, 0.5422, 0.5660, and 0.4340 in Tripoli. Significant difference in ABO and Rh D allele frequencies was found in Jadu, which indicated that Jadu’s population is not in Hardy–Weinberg equilibrium. This is the first study that documents the gene frequency for ABO and Rh D alleles and their prevalence of Jabal Nafusa region in Libya. The data in this study are of great importance to blood banks, blood transfusion services, genetics and anthropological studies in Libya.